A Histopathological Study of Endometrium in Abnormal Uterine Bleeding: A Retrospective Study - Pramana, Cipta; Damayanti, Lina; Petra Latuheru, Eunike; Rahayu Ningtyas, Dian; Michell,; Cynthia,; Angelina, Jessica; Lukas, Ario; Rizky Pramana, Dede; Gunarmi, (International Journal of Psychosocial Rehabilitation, 2020)
Background: Abnormal uterine bleeding (AUB) is a common gynecological complaint associated with considerable morbidity and significantly affects the patient’s family, personal, and social life. The study aimed to analyze the histomorphological patterns of endometrium in patients presenting with AUB and also to determine the incidence of AUB in various age groups.Methods: This type of research is a descriptive study with a cross-sectional approach. Data was taken from medical records of the patients with a diagnosis of abnormal uterine bleeding by dilatation and curettage and then by a histopathological laboratory examination at the K.R.M.T. Wongsonegoro Hospital in Semarang, Indonesia.Results: A total of 87 cases were analyzed. The patient’s age ranged from 19 to 68 years old. Body Mass Index (BMI) divided three groups: Normal weight: 27%; overweight: 35.6%; and obese: 36.8%. Endometrial hyperplasia was the most common histopathological finding and was seen in 29.9% of patients, followed by irregular shedding (24.13%), disorder proliferative pattern (17.24%), proliferative with glandular and stromal breakdown (9.19%), and progestin effect (6.89%). Statistical test results with a chi-square relationship between BMI and histopathological features is p = 0.290.Conclusion: Statistical test results showed no relationship between age and BMI with histopathological results. We found that endometrial hyperplasia is the commonest cause of abnormal uterine bleeding.